Cytomegalovirus Retinitis in an ALL Child during Maintenance Therapy Treated Successfully with Intravenous Ganciclovir - KOÇ, AHMET; KEPENEKLİ KADAYİFCİ, EDA (My University, 2014)
Purpose. In here we described cytomegalovirus retinitis (CMVR) in 12-year-old male patient with acute lymphoblastic leukemia (ALL) who was on maintenance phase therapy. Methods. He was referred to our clinic for seeing of spots with the right eye for 3 days. At presentation, his best corrected visual acuity was 20/20 in the right eye and 20/20 in the left eye. Slit-lamp biomicroscopic examination of the anterior chamber of the left eye was within normal limits, whereas we observed 3+ anterior chamber cellular reaction in the right eye. On retinal examination, we found active retinitis lesions (cream-colored lesions associated with hemorrhages) and perivascular cuffing in the retinal periphery in the right eye. Left eye was normal. Results. On the basis of clinical picture, we made the diagnosis of CMVR in the right eye. Vitreous aspiration was performed and 23096 copies/mL of CMV DNA was detected by polymerase chain reaction (PCR) technique. The patient was successfully treated with intravenous ganciclovir for two weeks and discharged with oral valganciclovir prophylaxis. Conclusion. CMVR should be in mind in children with ALL on maintenance phase therapy even in those without hematopoietic stem cell transplantation. These patients can be treated successfully by intravenous ganciclovir alone.